The Flipped Learning and Blendspace to Improve Pupils’ Speaking Skills - Santhanasamy, Cassandra; Yunus, Melor Md (Frontiers in Psychology, 2022)
During the Covid-19 pandemic, the continuity of teaching and learning session is very important to provide a sustainable education to all pupils. The most difficult aspect of language acquisition has always been the speaking component. Pupils’ lack of interest and the difficulty in teaching and practicing speaking skills in the traditional classroom are the main issues that hinders pupils’ speaking skills. Thus, the purpose of this study was to explore the flipped learning approach to improve primary school pupils’ speaking skills. In this study, Blendspace was used to support the flipped learning method in helping pupils improve their speaking skills. This study employed a mixed-method research design. Speaking pre-post-tests, questionnaires and interviews were used to collect data from Year 3 primary school students. The findings revealed that the use of Blendspace in teaching speaking has improved pupils’ speaking skills and the pupils were motivated to practice speaking inside and outside of classroom. Hence, the utilization of Blendspace in the flipped learning approach is an effective pedagogy to improve pupils’ speaking skills. The findings of this research would be useful for teachers and policymakers to assist pupils in enhancing their speaking abilities.